2018
DOI: 10.1016/j.addbeh.2018.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and facets linked with self-reported alcohol consumption and biomarkers of liver health

Abstract: This study adds multi-method evidence in support of a link between personality and health behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…Notably, the present study also revealed conscientiousness to exhibit a significant negative association with alcohol intake for males, which is in line with previous literature [19,43,44].…”
Section: Discussionsupporting
confidence: 93%
“…Notably, the present study also revealed conscientiousness to exhibit a significant negative association with alcohol intake for males, which is in line with previous literature [19,43,44].…”
Section: Discussionsupporting
confidence: 93%
“…The NEO-PI is the most comprehensive self-report questionnaire that measures the five-factor model of personality, in which neuroticism is included (Costa and McCrae, 1997 ; Xu and Potenza, 2012 ). The NEO-PI consists of 240 items and has been extensively validated (John and Kentle, 1991 ; Luchetti et al, 2018 ). It measures five major factors and 30 facets.…”
Section: Methodsmentioning
confidence: 99%
“…From a psychological point of view, evidence indicates that personality variables are clearly associated with alcohol consumption. Indeed, numerous works have related different patterns of alcohol consumption with different personality traits [4][5][6][7]. Considering the great variety of personality traits, the purpose of the present study is to explore which personality traits, specifically impulsive traits, have a greater predictive power on alcohol consumption in young people.…”
Section: Introductionmentioning
confidence: 98%